Large deviations for random evolutions with independent increments in a scheme of Levy approximation - Samoilenko, I.V. (Український математичний вісник, 2015)
Asymptotic analysis of the problem of large deviations for random evolutions with independent increments in the circuit of the L´evy approximation is carried out. Large deviations for random evolutions in the circuit of the L´evy approximation are determined by the exponential generator for a jump process with independent increments.